Leaf area estimation for Psychotria carthagenensis and Psychotria hoffmannseggiana as a function of linear leaf dimensions - Ribeiro, João Everthon da Silva; Coêlho, Ester dos Santos; Figueiredo, Francisco Romário Andrade; Pereira, Walter Esfrain; Albuquerque, Manoel Bandeira de (Acta Scientiarum. Biological Sciences, 2019)
Determining leaf area is important for studies involving plant growth and development. The aim of the present study was to obtain models for estimating leaf area of Psychotria carthagenensis and Psychotria hoffmannseggiana using linear measurements of leaf blades (length and width). Two hundred leaf blades of each species were collected in Parque Estadual Mata do Pau-Ferro in the municipality of Areia, Paraíba, Northeast Brazil. The equations evaluated for producing potential models included the following: linear, quadratic, potential and exponential. The criteria used to determine the best model(s) were as follows: high coefficient of determination (R²), low root-mean-square error (RMSE), low Akaike information criterion (AIC), high Willmott concordance index (d) and a BIAS ratio close to zero. All evaluated models satisfactorily estimated leaf area for the two species, but the equation ŷ = 0.6373 * LW0.9804 was the most appropriate for P. carthagenensis, while ŷ = 0.6235 * LW0.9712 was the most appropriate for P. hoffmannseggiana.